KEANEKARAGAMAN JENIS MANGROVE DI PANTAI MANIKIN KABUPATEN KUPANG TENGAH NUSA TENGGARA TIMUR - Iramaya Dilak, Hory (Universitas Cokroaminoto Palopo, 2024)
Mangroves are known to have various important roles and benefits, one of which is protecting the land area behind them. Research on mangrove diversity has never been carried out on Manikin Beach, so this research was carried out. The aim of this research is to determine the diversity of mangroves on Manikin Beach, Central Kupang Regency, East Nusa Tenggara. The research method is a descriptive method, with direct surveys in the field. Based on the research results, the species found in the mangrove ecosystem area consisted of 9 species, namely Rhizophora Sp, Lumnitzera littorea, Avicennia officinalis, Excoecaria agallocha, Sonneratia alba, Aegialitis annulata, Derris trifoliata, Sapium indicum Willd, and Laguncularis racemosa. The species diversity index value, namely 2.104, shows that the diversity of mangrove species on Manikin Beach is categorized into the medium category. The dominance index value obtained is 0.132, it can be said that the dominance of mangrove species is moderate. The evenness value is 0.957. This shows that the mangrove evenness index includes a level of evenness while the community is unstable. The mangrove species richness index is included in the low category because it has an average species richness level of 1,800.